UTILIZATION OF TIK-TOK AS A DA’WAH MEDIA OF KADAM SIDIK IN THE CONTEMPORARY ERA - Nidya Agustin Beni Prasetyo; Erwin; Nuris Asro'atul Hasanah; Abu Yazid Al Bustomi; Moh Ali Aziz (Universitas Islam Negeri Mataram, 2023)
This research aims to examine the phenomenon of Dakwah Kadam Sidik on the TikTok platform in the contemporary era. The research employs a qualitative descriptive methodology, focusing on content analysis of Kadam Sidik's dakwah videos and conducting direct interviews with Kadam Sidik as the primary data source. Additionally, the study provides a comprehensive review of literature on dakwah in the era of social media and relevant theories. The findings of this research are expected to offer a deeper understanding of effective dakwah strategies on TikTok, as well as the contribution of Dakwah Kadam Sidik in disseminating religious values through social media. The conclusions drawn from this research can serve as a foundation for developing more adaptive and contextual dakwah strategies in the digital era.